2015
DOI: 10.1002/stem.2082
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Determines the Propensity of Adult Hippocampal Neural Stem Cells to Autophagic Cell Death Following Insulin Withdrawal

Abstract: Programmed cell death (PCD) has significant effects on the function of neural stem cells (NSCs) during brain development and degeneration. We have previously reported that adult rat hippocampal neural stem (HCN) cells underwent autophagic cell death (ACD) rather than apoptosis following insulin withdrawal despite their intact apoptotic capabilities. Here, we report a switch in the mode of cell death in HCN cells with calpain as a critical determinant. In HCN cells, calpain 1 expression was barely detectable wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…Some authors have proposed very different roles for autophagy in the maintenance of adult rat hippocampal NSCs. Chung and coworkers found that rat hippocampal NSCs undergo autophagic cell death in response to insulin withdrawal despite the presence of intact apoptotic machinery, and that this effect is suppressed by the knockdown of Atg7 (Chung et al, 2015). Conversely, Yu and colleagues reported that the tight regulation of calpainsa family of calcium-dependent cytosolic proteasesby the proteasome and by Ca 2+ levels switches the mode of hippocampal NSC cell death from being autophagic, when calpain levels are low, to apoptotic, when calpains levels are high (Yu et al, 2008).…”
Section: Autophagy In Neural Stem Cellsmentioning
confidence: 99%
“…Some authors have proposed very different roles for autophagy in the maintenance of adult rat hippocampal NSCs. Chung and coworkers found that rat hippocampal NSCs undergo autophagic cell death in response to insulin withdrawal despite the presence of intact apoptotic machinery, and that this effect is suppressed by the knockdown of Atg7 (Chung et al, 2015). Conversely, Yu and colleagues reported that the tight regulation of calpainsa family of calcium-dependent cytosolic proteasesby the proteasome and by Ca 2+ levels switches the mode of hippocampal NSC cell death from being autophagic, when calpain levels are low, to apoptotic, when calpains levels are high (Yu et al, 2008).…”
Section: Autophagy In Neural Stem Cellsmentioning
confidence: 99%
“…Autophagy is up‐regulated during cell differentiation in neuroblastoma cells and its inhibition prevents the differentiation of neurones, a process that is also regulated by mTOR . Several autophagy‐related proteins, including ambra1, beclin 1, ATG5, and calpain, have recently been implicated in regulating AHN . Because CR and acyl‐ghrelin regulate both autophagy and AHN, albeit in different brain regions, it is reasonable to suggest that CR and acyl‐ghrelin‐mediated regulation of AHN may be influenced by autophagy.…”
Section: Calorie Restriction Regulates Adult Hippocampal Neurogenesismentioning
confidence: 99%
“…146 Several autophagy-related proteins, including ambra1, beclin 1, ATG5, and calpain, have recently been implicated in regulating AHN. [147][148][149] Because CR and acyl-ghrelin regulate both autophagy and AHN, albeit in different brain regions, it is reasonable to suggest that CR and acyl-ghrelin-mediated regulation of AHN may be influenced by autophagy.…”
Section: Calorie Restriction Regulates Adult Hippocampal Neurogenesismentioning
confidence: 99%
“…Importantly, cell death rate was significantly decreased with knockdown of Atg7 in insulin-deprived HCN cells. Of note, high calpain activity switched the cell death mode from ACD to apoptosis [ 14 ]. Interestingly, activation of glycogen synthase kinase-3β (GSK-3β), one of the key signaling molecules in regulation of neuronal apoptosis, also promoted ACD, not apoptosis, in insulin-deprived HCN cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%